The summer sisters - Richardson, Sara (Romance fiction writer) (Juniper Springs series, 2021)
"The Buchanan sisters share everything -- even ownership of their beloved Juniper Inn. But their mother and Aunt Sassy won't even stay in the same state, and no one knows the story behind the sisters' decades-long feud. When youngest sister, Rose, plans the inn's grand re-opening for the same weekend as Sassy's 70th birthday's party, a family reunion seems unavoidable. Only Rose needs help from a certain handsome, if surly, hardware store owner to pull off an extravagant celebration. The sparks between them are undeniable, but Rose can't help suspecting he's hiding something from her . . . After a heartbreaking end to her marriage, Dahlia Buchanan and her kids have built a new life in Colorado. She's started flirting with the town doctor, but how does she know she's ready to open her heart again? When her youngest daughter cleverly maneuvers her to Juniper Springs on her estranged sister's birthday, Lillian Buchanan has no choice but to finally face her once-beloved sibling. But some wounds are just too deep to heal. And what will her daughters do when the family secrets she's tried so hard to hide come flooding into the open?"--